Variación de los flujos de dióxido de carbono en épocas de vaciante y creciente en los fustes de los árboles de la turbera de Buena Vista, Loreto, Perú – 2023 - García Noriega, Sergio Aroldo (2025)
This research seeks to determine the variation of carbon dioxide flux in tree trunks during periods of low and high river flow in the Buena Vista peat bog. A descriptive, quantitative, correlational, and basic-level methodology was used. 25 trees were measured with closed cameras (caterpillars) in the months of June, August, October, November, December, and January. The averages of the flow in trunks were quantified; water level values were taken from the meteorological station located in Tamshiyacu. In June, the river level was 116.48 m, in August it was 113.31 m and in October it was 111.23 m. Water levels drop and the CO2 flux increases only slightly; in June (31.92 µmol/m2/min), in August (49.74 µmol/m2/min), and in October it drops (45.68 µmol/m2/min). Now at the water levels starting in November 114.34 m, December 115.76 m, January 117.65 m, it begins to increase and the CO2 flux also, November (46.75 µmol/m2/min), December (38.76 µmol/m2/min) with a small drop in this month and in January being the strong flood, it reached (72.88 µmol/m2/min). We performed a 3 degree polynomial correlation with an R2 value of 0.8906 which means that river water levels have a strong influence on carbon dioxide fluxes. The Student 's t test indicated a flux of 41.92 µmol/m2/min in ebb and flow and 53.45 µmol/m2/min in flooding, evidencing that the higher the water level, the greater the CO2 flux in the tree trunks.